Analysis of the proficiency of fully connected neural networks in the process of classifying digital images - Janke, Jonathan (2022)
Janke, J., Castelli, M., & Popovič, A. (2019). Analysis of the proficiency of fully connected neural networks in the process of classifying digital images: Benchmark of different classification algorithms on high-level image features from convolutional layers. Expert Systems with Applications, 135, 12-38. https://doi.org/10.1016/j.eswa.2019.05.058